Women and austerity in Italy - Segnana,Maria Luigia (2015)
The paper considers how the severe and long downturn in the first phase of the crisis, followed by fiscal consolidation (austerity policies) in its second phase, have heavily impacted on women and men in Italy. It argues that the effects are considerably different - in terms of job loss, income loss, impact on jobs quality and unpaid work - because of the gendered nature of the family-employment system and the characteristics of the Italian social model.